Expression of C5aR （CD88） of synoviocytes isolated from patients with rheumatoid arthritis and osteoarthritis - 袁国华 魏锦 周京国 胡宏 唐中 张国元 (Chinese medical journal, 2003)
Objective To investigate the expression of anaphylatoxin receptor C5aR (CD88) in synoviocytes from patients with rheumatoid arthritis (RA) and osteoarthritis (OA).Methods The expression of C5aR was assessed in synoviocytes isolated from 27 RA and 12 OA patients using reverse transcription-polymerase chain reactions (RT-PCR), flow cytometry, and immunofluorescence analysis. The effects of C5a on the release of tumor necrosis factor a (TNFα)from synoviocytes were assayed using enzyme-linked immunosorbent assays (ELISA).Results C5aR mRNA was detected in 24 of 27 samples from RA patients, and 10 of 12 samples from OA patients. Flow cytometric analysis and immunofluorescence study demonstrated the cell surface expression of C5aR in a significant proportion of synoviocytes from both RA and OA patients,and the level of C5aR expression in synoviocytes was significantly correlated with joint swelling,erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) in RA patients. Finally,interaction of C5aR with its ligand C5a was shown to enhance lipopolysaccharide (LPS)-induced TNFα release from synoviocytes.Conclusions The expression of C5aR in synoviocytes from inflammatory joint diseases and also the induction of TNFα release in activated synovicytes by the interaction of C5a and C5aR suggest that the C5a/C5aR system may play an important role in joint inflammation process.